The Relationship among Organizational Identification, Flow Experience, Intention to Continue Participation, and Recommendation Intention of Taekwon Gymnastics Participant - You-Lee Choi; Il-Gwang Kim; Jongchul Park (Cheyuk gwahag yeon-gu, 2022)
PURPOSE Taekwon gymnastics is expected to be a program that can overcome the management difficulties currently faced by Taekwondo gyms and contribute to the expansion of Taekwondo base. Therefore, this study aimed to examine the relationship among organizational identification, flow experience, intention to continue participation, and recommendation intention of Taekwon gymnastics participants. METHODS In this study, data was collected from 313 teenagers participating in Taekwon gymnastics at Taekwondo gyms in the metropolitan area from September 10 to 24, 2021. A total of 267 questionnaires were selected as the final sample, and data analysis was conducted using SPSS 23.0 and AMOS 23.0. RESULTS Organizational identification had a significant effect on flow experience, challenge only had a positive effect on intention to continue participation, flow experience did not significantly affect recommendation intention, and intention to continue participation had a significant effect on recommendation intention. CONCLUSIONS The results of this study confirmed that organizational identification can contribute to improving inner pleasure and self-esteem, and it is necessary to examine the role of factors that can mediate the relationship between flow experience and behavioral intention in the future. Furthermore, managers of Taekwondo gyms should hold various events that can inspire teenagers’ sense of challenge to encourage intention to continue participation.